Effects of different temperatures on growth and intestinal microbial composition of juvenile Eriocheir sinensis - Liang, Meng; Feng, Wenrong; Chen, Xue; Tang, Yongkai; Li, Jianlin; Li, Wenjing (Frontiers in Physiology, 2023)
The change of temperature will change the composition of intestinal microorganisms of juvenile Eriocheir sinensis, and the composition of intestinal microorganisms will affect the growth and development of juvenile crabs. In order to explore the relationship between intestinal microorganisms and growth of E. sinensis at different temperatures, the status of growth and intestinal microflora of juvenile E. sinensis reared at different water temperatures (15 ℃, 23 ℃, 30 ℃) were compared in this study. The results showed that the respective survival rate of juvenile E. sinensis in three water temperature groups was 100%, 87.5% and 64.44%.Moreover, the molting rate increased with an increase in water temperature, which was at 0%, 10% and 71.11% for the three respective temperature groups. The average weight gain rate showed an overall increasing trend with the increase of water temperature. Moreover, the final fatness of the crabs in the 30 ℃ water temperature group was significantly lower than that in 15 ℃ and 23 ℃ (P < 0.05); there was no significant difference in the liver-to-body ratio among the three groups. The results of the alpha diversity analysis of the 16S rRNA data revealed that there was no significant difference in the intestinal microbial abundance among the three water temperature groups; however, the intestinal microbial diversity in 23 ℃ water temperature group was significantly lower than that in the 15 ℃ and 30 ℃. At the phylum level, the dominant flora of the three